Allelopathic Activity of the Hydrolate and Water Decoction of Brachiaria humidicola (Rendle) Plant Parts on the Germination of Four Tropical Leguminous Species. (3rd September 2012) - Ribeiro, Roberta Cristiane; de Carvalho, Mário Geraldo; Lopes, Higino Marcos; Rossiello, Roberto Oscar Pereyra; Barbieri Junior, Élio
Abstract : Knowledge of allelopathic interactions between grasses and legumes can contribute for the successful establishment of mixed tropical pastures in Brazil. The purpose of this work was to evaluate the allelopathic effect of the hydrolate and water decoction of Brachiaria humidicola (Rendle) plant parts (root, shoot, and seeds) on four tropical forage legumes Stylosanthes spp. cv. Campo Grande, Macrotyloma axillare, Calopogonium mucunoides, Desmodium ovalifolium, and on lettuce ( Lactuca sativa L.), this last species used as a sensitivity standard in allelopathic bioassays. The results obtained for roots and shoots showed, in the case of hydrolate, the highest inhibitory effect on germination rates of the receiving species, while seed hydrolates had a stimulating effect depending on the legume species. In contrast, water decoction extracts had the highest inhibitory effects on root and seed fraction, and the lowest on the shoot fraction. Regarding the receiving species, germination percentages of M. axillare showed higher tolerance to inhibitory effects of the aqueous extracts of B. humidicola, while D. ovalifolium showed the highest sensitivity.